DESCRIPTIVE ANALYSIS OF HIGHER EDUCATION LEADERSHIP: Character and Ability to Lead - Finatariani , Endah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
In organizational science, a leader is seen as an embodiment of the organization, because he has the authority to use all available resources, including human beings. Therefore, the impact of the leadership role is very large. In other words, from a managerial perspective, organizations must be careful and thorough in appointing a leader, because the consequences/risks that arise are very large for the achievement of organizational goals. Based on this, this research was conducted to look at the character and leadership abilities of the head of the study program at Pamulang University. To prove this goal, a descriptive quantitative approach is used. The research informants were 75 study program developer lecturers, using a simple random sample technique. The results of the study explained that in general the leadership character of the head of the study program at Pamulang University was democratic, with the advantage of being open to various criticisms, always involving lecturers in decision making, and inviting all lecturers to participate in implementing policies. In addition, the personality of the head of the study program at Pamulang university is humane and religious, so there is no distance in interacting with all existing stakeholders.